2016
DOI: 10.1007/s00276-016-1637-6
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric study of anterior and posterior elbow endoscopy portals for endoscopic distal biceps repair: comparative anatomy-at-risk

Abstract: Portals 1 (parabiceps portal) and 5 (distal posterior) can be safely placed for endoscopic access to the DBT. Portal 4 (open distal anterior) may be used after careful open dissection and under direct vision. Portals 2 and 3 are not recommended for elbow endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Recent articles seem to confirm the safety of biceps endoscopy and showed the feasibility through a single anterior incision. 69 , 70…”
Section: Treatment Of Distal Biceps Tendon Injurymentioning
confidence: 99%
“…Recent articles seem to confirm the safety of biceps endoscopy and showed the feasibility through a single anterior incision. 69 , 70…”
Section: Treatment Of Distal Biceps Tendon Injurymentioning
confidence: 99%
“…Similarly, the procedure should be avoided in patients with vascular anomalies and malunited fractures. Familiarity with the anatomical course of major neurovascular structures and their dynamic relationship to DBT is necessary to prevent any iatrogenic complications [3][4][5].…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…Bhatia et al evaluated five potential portal sites above and below the elbow crease for elbow endoscopy [7]. The study showed that the anterior portal placed above the elbow crease (parabiceps portal) was safe, while the three anterior portals placed at different levels below the elbow crease were significantly closer to neurovascular structures.…”
Section: Neurovascular Anatomy At-riskmentioning
confidence: 99%
“…Familiarity with the morphometric anatomy and relationships of DBT with surrounding structures is crucial for optimal outcomes after open or endoscopic surgery for biceps pathology. The insertional anatomy of DBT and its dynamic relationship to the proximal radioulnar space and neurovascular structures have been quantified in recent studies, and this knowledge is crucial to understand safe placement of portals and incisions for open/endoscopic reconstruction techniques [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%